MARKET BASKET ANALYST BASED ON WEBSITE USING ECLAT ALGORITHM (CASE STUDY POLA PHARMACY) - Edgar Lawrence; Bagus Mulyawan; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Market basket analyst is a data mining technique todiscover associations between datasets. Association rulemining identifies a relationship between a large set ofdata item. When a large quantity of data is constantlyobtained and stored in database, several industries arebecoming concerned about mining association rulesfrom their databases. Market basket analysis examinescustomer buying patterns by identifying associationsamong various items that customers place in theirshopping baskets. It is helpful to examine customerpurchasing behaviour and assists in increasing sales. Sothis system is intended to develop a system for marketbasket analysis on Pola Pharmacy which generateassociation rules among itemsets with the use of ECLAT(Equivalence Class Transformation) algorithm. Thissystem supports the decision making process for amarket expert.